Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-2982.2011.01784.x
|View full text |Cite
|
Sign up to set email alerts
|

Movement based artifacts may contaminate extracellular electrical recordings from GI muscles

Abstract: Background Electrical slow waves drive peristaltic contractions in the stomach and facilitate gastric emptying. In gastroparesis and other disorders associated with altered gastric emptying, motility defects have been related to altered slow wave frequency and disordered propagation. Experimental and clinical measurements of slow waves are made with extracellular or abdominal surface recording. Methods We tested the consequences of muscle contractions and movement on biopotentials recorded from murine gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 51 publications
3
64
2
Order By: Relevance
“…[38][39][40] However, recordings via this technique are due largely to movement artifacts rather than to valid electrophysiological recordings of membrane currents (slow waves). 41 For this reason we employed motility imaging so we could record the progress of gastric peristaltic contractions unambiguously. These studies clearly demonstrated development of functional uncoupling and disruption of gastric peristalsis in response to cholinesterase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] However, recordings via this technique are due largely to movement artifacts rather than to valid electrophysiological recordings of membrane currents (slow waves). 41 For this reason we employed motility imaging so we could record the progress of gastric peristaltic contractions unambiguously. These studies clearly demonstrated development of functional uncoupling and disruption of gastric peristalsis in response to cholinesterase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Since then the recording of slow waves by extracellular and intracellular electrodes has served as an important tool to understand gut motility function in health and disease. Two recent publications raised questions about the fidelity of extracellular electrodes in recording slow waves (Bayguinov et al 2011;Rhee et al 2011). The authors used extracellular and intracellular electrodes to record from isolated muscle strips or gastric sheets.…”
Section: Email: Sksarna@utmbedumentioning
confidence: 99%
“…In describing our rationale for the technology chosen, we made reference to the unsuitability of extracellular electrical recording as a means to measure changes in slow waves, because movement artifacts dominate these measurements. 2 In a previous study we found that when movements are blocked, under conditions in which slow waves are unaffected, the signals recorded with extracellular metal electrodes and many have attributed to electrophysiological events (slow waves), are inhibited. 2 Thus the signals monitored by extracellular electrodes are largely artifacts of movement and do not represent authentic slow wave activity.…”
mentioning
confidence: 92%
“…2 In a previous study we found that when movements are blocked, under conditions in which slow waves are unaffected, the signals recorded with extracellular metal electrodes and many have attributed to electrophysiological events (slow waves), are inhibited. 2 Thus the signals monitored by extracellular electrodes are largely artifacts of movement and do not represent authentic slow wave activity. In light of these observations, which have been reproduced in mouse, dog, monkey and human gastric muscles when movement is suppressed, it is important for studies utilizing extracellular electrical recording to be accompanied by rigorous tests insuring that the electrical signals claimed to be slow waves persist after movement is stabilized.…”
mentioning
confidence: 92%
See 1 more Smart Citation